Intercropping in Okra for Sustainable Vegetable Production - Choudhuri, P.; Jana, J. C. (International Journal of Bio-resource and Stress Management, 2023)
A field experiment was conducted at the Instructional Farm of UBKV during rabi seasons of 2008 and 2009 to assess intercropping effect in okra with an objective to generate more income from the farm through increased cropping intensity and complete and economical use of natural resources by combining nine different treatment combinations of different intercrops like cowpea, amaranthus, radish and palak in 1:1 row ratio. The trial was laid out in randomized block design (RBD) with four replications. Experimental results indicated that sole cropping of okra recorded significantly maximum values for most of the vegetative parameters. Sole cropping of okra recorded maximum number of marketable fruits plot-1 (1502.81), maximum fruit weight (17.11 g) and highest yield ha-1 (11.54 t). However, maximum okra equivalent yield ha-1 (15.67 t) was observed in okra+cowpea intercropping system. Minimum value for the same (9.02 tha-1) was recorded in okra+radish intercropping system. The study revealed that ascorbic acid content of the okra fruit was not significantly affected due to intercropping. Okra+cowpea intercropping system was found best user of biological resources as it recorded maximum values for LER (1.56), RCC (13.75) and lower values of aggressivity (-0.14) and competitive ratio (0.93). Economic analysis also showed that okra+cowpea intercropping system was most remunerative as it recorded highest net return and B:C ratio (` 1,35,891.50 and 2.61, respectively).Based on the findings, growing of cowpea with okra may be adjudged as the best intercropfor sustainable vegetable production.